A COMPARATIVE STUDY OF KINSHIP APHORISMS IN ENGLISH AND UZBEK LANGUAGES (Scientific journal of the Fergana State University, 2024)
This comparative study examines kinship aphorisms in English and Uzbek in order to uncover cultural and linguistic nuances in the expression of familial relationships. The study analyses the semantic, syntactic and pragmatic features of kinship terms and their use in proverbs using a corpus of aphorisms from both languages. Qualitative and quantitative analyses reveal similarities and differences in the conceptualisation of kinship in the two languages, shedding light on the cultural values, social norms and linguistic structures underpinning these expressions.